Israel : Staff Report for 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
This 2013 Article IV consultation highlights the moderate growth of the economy of Israel. Abstracting from the impact of new large-scale natural gas production, GDP growth is estimated to have moderated to about 2.5 percent in 2013, owing in large part to weak investment and exports. Some pickup is expected in 2014, but the underlying momentum is weaker than before. Despite notable progress, Israel's public debt remains high, while continued housing price increases pose risks of a boom-bust cycle in the housing market. The key policy challenge is to maintain near-term growth at potential, while preventing the buildup of imbalances, strengthening resilience to shocks, and ensuring long-term sustainability.